PENGARUH LOKASI, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DIWARUNG KOPI NETRAL RANTAUPRAPAT (Study Kasus Konsumen Rantau Prapat) - Suyanti, Suyanti (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
This study aims to analyze the effect of Location on Customer Satisfaction at Rantauprapat Neutral Coffee Shop. To analyze the effect of Product Quality on Customer Satisfaction at Rantauprapat Neutral Coffee Shop. To analyze Service Quality on Satisfaction at Rantauprapat Neutral Coffee Shop. This research was conducted at Warung Kopi Neutral Rantauprapat with a sample of 245 people from 633 populations. Data collection techniques were carried out by questionnaires or primary data. Data analysis techniques used descriptive statistics and multiple linear regression analysis. The results showed that the variables of Location, Product Quality and Service Quality simultaneously had a positive and significant effect on Customer Satisfaction. Fcount 7 74,931> Ftable 2.65 with a significant value of 0,000, partially location had a positive and significant effect on Consumer Satisfaction, the tcount was 9,115> ttable 1.65 The probability of t is 0.000 <0.05, partially Product Quality has a positive and significant effect on Customer Satisfaction, the value of tcount 1.748> ttable 1.65 is obtained, Service Quality has a positive and significant effect on Customer Satisfaction, the value of tcount is 6.475> t table 1.65.